Can Intraoperative Low-Dose R,S-Ketamine Prevent Depressive Symptoms After Surgery? The First Meta-Analysis of Clinical Trials - Pang, Liwei; Cui, Meiying; Dai, Wanling; Kong, Jing; Chen, Hongzhi; Wu, Shuodong (Frontiers in Pharmacology, 2020)
Background: Postoperative depression is a common complication after surgery that profoundly affects recovery and prognosis. New research indicates that (R,S)-ketamine is a potent antidepressant that exerts a rapid and sustained antidepressive effect. However, there is no consensus on whether intraoperative low-dose (R,S)-ketamine prevents postoperative depression. Objectives: This study aimed to investigate the safety, feasibility, and short-term complications of intraoperative low-dose (R,S)-ketamine in preventing postoperative depressive symptoms. Methods: The Web of Science, Cochrane, PubMed, and CNKI databases were systematically searched (last search February 28, 2020) to identify studies involving ketamine. Sensitivity and metaregression analyses were performed to identify potential confounders. The meta-analysis was performed using Review Manager 5.3. Results: A total of 13 studies (seven in Chinese and six in English) representing 1,148 cases of patients who were treated with (R,S)-ketamine and 874 cases of patients who received other treatments were included in the meta-analysis. Anesthesia duration and blood loss did not significantly differ between the two groups, demonstrating that (R,S)-ketamine was safe (odds ratio,OR: 0.27; 95% CI: −1.14 to 1.68; P = 0.71) for prophylactic treatment of postoperative depression. Blood loss (OR: −1.83; 95% CI: −8.34 to 4.68; P = 0.58), the number of postoperative depressive patients (95% CI: 0.8–1.07; P = 0.08; (R,S)-ketamine: control = 12.9%:15.8%), and postoperative complications (OR: 0.83, 95% CI: 0.44–1.58; P = 0.57; (R,S)-ketamine: control = 19.3%:19.3%) were all similar across groups. Intra-operative low-dose (R,S)-ketamine reduced extubation time (OR: −2.84; 95% CI: −5.48 to −0.21; P = 0.03). Conclusions: The prophylactic anti-depressant effect of (R,S)-ketamine did not significantly differ between the (R,S)-ketamine and control groups in patients undergoing general or spinal anesthesia. However, (R,S)-ketamine use led to a higher incidence of adverse reactions in patients under 40 years of age who underwent a Cesarean section under spinal anesthesia.